Laboratory to bench-scale performance evaluation of a biphasic solvent for low-concentration CO2 capture from simulated gas turbine flue gas - Hang Yu; Sining Kong; Wenrui Li; Yitao Gan; Lijian Jin; Ruiyang Gao; Fan Zhang; Linjun Yang (Chemical Engineering Journal, 2026)

Janus cellulose nanofiber foam-based flexible triboelectric nanogenerator for wearables - Jingqiu Wang; Xiaojun Li; Peiyao He; Dong Lv; Min Wang; Linjun Zou; Hong Wang; Jian Li; Likun Gao (Carbohydrate Polymers, 2026)

Waste heat recovery from flue gas inside MEA-based CO2 capture processes using heat pump technologies and associated environmental impact assessment - Lijian Jin; Debo Li; Lingxiao Zhan; Hang Yu; Wenrui Li; Yitao Gan; Sining Kong; Ruiyang Gao; Jinjin Li; Heng Chen; Linjun Yang (Journal of Cleaner Production, 2026)

An overview of the formation mechanism characteristics of glacial lake outburst floods in Tibet, China - Jiankang Liu; Ruilin Xu; Linjun Zhou; Ting Yi; Jianxun Liu; Jiajia Zhang; Bo Gao; Yuanling Li; Hai Huang (Natural Hazards, 2026)

Stage-specific FeS-mediated regulation of Paracoccus denitrificans during carbon consumption by machine learning-assisted comparative proteomics - Linjun Gao; Wenyu Wang; Xuan Huang; Yunyi Zha; Yongzhi Zhang; Ping Ye; Rui Wan (Environmental Research, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

High humidity-resisted all-wood-based triboelectric nanogenerator for energy harvesting and human motion monitoring - Peiyao He; Xiaojun Li; Min Wang; Dong Lv; Jingqiu Wang; Linjun Zou; Ruixiang Cheng; Ran Yin; Xiang Chi; Jian Li; Likun Gao (Chemical Engineering Journal, 2025)

Synthesis of Cu2O/CuZnAl-LDHs heterojunction photocatalyst with enhanced antibacterial efficiency for personal protective equipment - Tian Sun; Xiangkun Ran; Mingyue Cao; Jiaqi Liu; Yanrui Su; Linjun Duan; Dan Liang; Zihao Xia; Wa Gao; Hanqing Zhao (Environmental Research, 2025)

Metagenomic insights into the assembly, function, and key taxa of bacterial community in full-scale pesticide wastewater treatment processes - Xiaoxiao Wang; Linjun Gao; Shuya Wang; Xian Zhang; Ruonan Feng; Shuyu Jia (Environmental Research, 2025)

Refractory wastewater shapes bacterial assembly and key taxa during long-term acclimatization - Linjun Gao; Xiaoxiao Wang; Yujie Wang; Xu Xu; Yu Miao; Peng Shi; Shuyu Jia (Water Research, 2024)

Prevalence of antibiotics, antibiotic resistance genes, and their associations in municipal wastewater treatment plants along the Yangtze River basin, China - Yangyang Zhang; Yifan Hu; Xiuwen Li; Linjun Gao; Shuya Wang; Shuyu Jia; Peng Shi; Aimin Li (Environmental Pollution, 2024)

Deciphering the core bacterial community structure and function and their response to environmental factors in activated sludge from pharmaceutical wastewater treatment plants - Jinli Zheng; Xin Huang; Linjun Gao; Xu Xu; Lijun Hou; Tianming Cai; Shuyu Jia (Environmental Pollution, 2024)

Deciphering the dynamics and driving mechanisms of high-risk antibiotic resistome in size-fractionated bacterial community during drinking water chlorination via metagenomic analysis - Shuya Wang; Yan Zhuang; Linjun Gao; Hongbin Huang; Xian Zhang; Shuyu Jia; Peng Shi; Xu-Xiang Zhang (Journal of Hazardous Materials, 2024)

Free-living lifestyle preferences drive the antibiotic resistance promotion during drinking water chlorination - Shuyu Jia; Shuya Wang; Yan Zhuang; Linjun Gao; Xian Zhang; Lin Ye; Xu-Xiang Zhang; Peng Shi (Water Research, 2024)

Metagenomic analysis reveals the distribution, function, and bacterial hosts of degradation genes in activated sludge from industrial wastewater treatment plants - Linjun Gao; Shuya Wang; Xu Xu; Jinli Zheng; Tianming Cai; Shuyu Jia (Environmental Pollution, 2024)

A self-healing poly(ionic liquid) block copolymer electrolyte enabled by synergetic dual ion-dipole interactions - Linjun Gao; Wenbin Jiang; Xiaorong Zhang; Yuxue Sun; Kai Chen; Wenliang Li; Haiming Xie; Jun Liu (Chemical Engineering Journal, 2024)

Geographical and temporal variation of multiple paternity in invasive mosquitofish ( Gambusia holbrooki , Gambusia affinis ) - Jiancao Gao; Francesco Santi; Linjun Zhou; Xiaoqin Wang; Rüdiger Riesch; Martin Plath (Molecular Ecology, 2019)
Multiple paternity (MP) increases offspring's genetic variability, which could be linked to invasive species' evolvability in novel distribution ranges. Shifts in MP can be adaptive, with greater MP in harsher/colder environments or towards the end of the reproductive season, but climate could also affect MP indirectly via its effect on reproductive life histories. We tested these hypotheses by genotyping N = 2,903 offspring from N = 306 broods of two closely related livebearing fishes, Gambusia holbrooki and Gambusia affinis . We sampled pregnant females across latitudinal gradients in their invasive ranges in Europe and China, and found more sires per brood and a greater reproductive skew towards northern sampling sites. Moreover, examining monthly sampling from two G. affinis populations, we found MP rates to vary across the reproductive season in a northern Chinese, but not in a southern Chinese population. While our results confirm an increase of MP in harsher/more unpredictable environments, path analysis indicated that, in both cases, the effects of climate are likely to be indirect, mediated by altered life histories. In both species, which rank amongst the 100 most invasive species worldwide, higher MP at the northern edge of their distribution probably increases their invasive potential and favours range expansions, especially in light of the predicted temperature increases due to global climate changes.